1956
DOI: 10.2307/1951334
|View full text |Cite
|
Sign up to set email alerts
|

State Patronage in a Rural County

Abstract: The use of public employment for political patronage is an ancient phenomenon seldom studied by political scientists in systematic and objective detail. Texts and treatises on political parties reckon with the subject, but usually support their generalizations and conclusions with illustrations rather than comprehensive evidence. Detailed studies date back to the muck-raking period, and deal chiefly with large metropolitan centers. The role of patronage in maintaining the thousands of rural and small city part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Surveys of patronage recipients often find that they were not particularly active in politics either before or after receiving their jobs (e.g. Sorauf, 1956;Johnston, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of patronage recipients often find that they were not particularly active in politics either before or after receiving their jobs (e.g. Sorauf, 1956;Johnston, 1979).…”
mentioning
confidence: 99%
“…Again, by definition, the entrenched party is in power more often than 30 Sorauf (1956) found that nearly 80% of the patronage employees in Centre County, Pennsylvania, claimed to have made a campaign contribution to the party. A 1962 study of Utah found that 33% of patronage employees made campaign contributions "regularly" or "sometimes, especially during campaigns," but only 7% of civil service employees did so (Gordon, et al, 1962).…”
mentioning
confidence: 99%
“…3. However, Sorauf (1956) does show that the vast majority of Pennsylvania county workers he interviewed changed their party affiliation in order to possibly regain the highway crew positions from which they were fired. 4.…”
Section: IVmentioning
confidence: 98%
“…The state party organizations allowed governors to retain control of patronage jobs both at the state and the local level. Sorauf's (1956)…”
Section: Patronage and Reform In Us Statesmentioning
confidence: 99%